Russia’s War with Ukraine and its Consequences FOR NATO - Gryz, Jarosław (Roczniki Nauk Społecznych, 2024)
The second phase of Russia’s war against Ukraine, launched on 24 February 2022, prompts us to take up the issues of “lessons learned” for NATO, as an alliance, and for the Member States in the context of ensuring collective defense and preparing armed forces for it. In addition, to verify the ways of generating readiness of the societies of the broadly defined West, with the participation of South Korea and Japan, to confront the challenges related to the efforts of the Russian Federation and China to revise the existing international security architecture, and to adapt NATO to new conditions. It concerns the fundamental conclusions from strategic, operational and tactical activities related to the use by the Russian Federation of its armed forces as a tool of policy against Ukraine and the North Atlantic Alliance and the European Union. The aim of the study is to analyze strategic, operational and tactical activities in terms of the identified solutions that the parties to the war have carried out and implemented against each other, indicating those that should potentially be adapted by NATO.